The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ma12244205
|View full text |Cite
|
Sign up to set email alerts
|

Study of Edge and Screw Dislocation Density in GaN/Al2O3 Heterostructure

Abstract: This study assesses the characteristics (edge and screw dislocation density) of a commercially available GaN/AlN/Al2O3 wafer. The heterostructure was evaluated by means of high-resolution X-ray diffraction (HR-XRD), high-resolution transmission electron microscopy (HR-TEM), and Doppler-Broadening Spectroscopy (DBS). The results were mathematically modeled to extract defect densities and defect correlation lengths in the GaN film. The structure of the GaN film, AlN buffer, Al2O3 substrate and their growth relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…The results which summarize the characteristics of the GaN layers listed in this study along with previously reported results [ 13 , 14 ] are shown in Table 2 . Additionally, Figure 4 c,d show the omega scans for (0004) and ( ) planes for GaN films grown on (111) 3C-SiC, (0001) Al 2 O 3 , and (111) Si substrates [ 13 , 14 ].…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…The results which summarize the characteristics of the GaN layers listed in this study along with previously reported results [ 13 , 14 ] are shown in Table 2 . Additionally, Figure 4 c,d show the omega scans for (0004) and ( ) planes for GaN films grown on (111) 3C-SiC, (0001) Al 2 O 3 , and (111) Si substrates [ 13 , 14 ].…”
Section: Resultssupporting
confidence: 52%
“…Our attempts to fit the experimental data using a three-layer model resulted in physically incorrect data, so a four-layer model was proposed instead, thereby splitting the GaN film into two sublayers (i.e., GaN1 and GaN2). A detailed explanation why the three-layer model results are incorrect is given in references [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the process of GaN growth, the large lattice mismatch of GaN with its substrate (silicon carbide (SiC) or sapphire) is inevitable. In addition, there are varieties of defects appearing in the whole fabrication process, including native point defects and impurities, such as C, O, H, as well as dislocations [ 7 , 8 ]. Therefore, it is still a big challenge to improve the performance of GaN-based devices.…”
Section: Introductionmentioning
confidence: 99%